2021
DOI: 10.3390/su13063030
|View full text |Cite
|
Sign up to set email alerts
|

Travel Mode of Commuting in Context of Subjective Well-Being—Experience from Slovakia

Abstract: This article deals with commuting to and from work of workers in Slovakia as a part of traveling and its impact on private life of commuters. It provides a more comprehensive view on the socio-demographic determinants which affect the travel mode choice. Furthermore, the study offers several evaluations of the impact on the subjective well-being of commuters. The aim of the article is to review demographic and economic determinants influencing the travel mode choice and to determine its impact on the subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…In the paper, it was stated that currently the research and practice of the green transport system is only at the initial stage and requires an indepth analysis and identification of the construction of a green transport system in international cities. Mazurova et al (2021) presented interesting results of the survey on green transport conducted among the inhabitants of Slovakia. They found that respondents were most satisfied with commuting by bike or on foot and most dissatisfied with commuting by public transport, indicating that they feel the need to implement sustainable and "green" transport infrastructure in their country.…”
Section: Discussionmentioning
confidence: 99%
“…In the paper, it was stated that currently the research and practice of the green transport system is only at the initial stage and requires an indepth analysis and identification of the construction of a green transport system in international cities. Mazurova et al (2021) presented interesting results of the survey on green transport conducted among the inhabitants of Slovakia. They found that respondents were most satisfied with commuting by bike or on foot and most dissatisfied with commuting by public transport, indicating that they feel the need to implement sustainable and "green" transport infrastructure in their country.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the participation or engagement in a diverse set of activities by individuals on a daily basis, activities are categorized as mandatory and discretionary activities, which are further classified as leisure and maintenance activities [1]. In addition, certain activities are carried out at home and are referred to as in-home (IH) activities, and others are outof-home (OH) activities.…”
Section: Introductionmentioning
confidence: 99%
“…The factors affecting commuting satisfaction mainly include the commuting time [8,9], commuting mode [10][11][12][13], built environment [14,15], service level [16,17], and perceived attitude [18,19]. For the commuting mode, there are a few reasons why walking or cycling are associated with higher satisfaction, such as moderate commuting times and lower commuting costs [20], more exposure to green space [21], increased social interaction, and the promotion of physical and mental health [22]. Congestion is the reason for low satisfaction with car commuting [23,24].…”
Section: Introductionmentioning
confidence: 99%